State and Problems of Thermal and Electricity Generating Capacity Pertaining to Power System of Republic of Iraq - A. V. Sednin; Nazar N. Qadame Hossene (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers state of thermal power plants and power system of theRepublicof Iraq. The analysis of capital equipment, fuel consumption, technological schemes and operating modes of power plants has been carried out and main problems have been determined in the paper. For restoration of a power supply system of theRepublicofIraqand provision of internal electric power demand it is necessary to elaborate a complex of measures directed on construction of new generating sources and restoration of power lines.